IT Service Management: Implementation of ITIL Framework in Modern Organizations - Aditya Akbar; Rafael Verdyansyah Pratama; Cahyo Purnomo; Muhammad Rifaldi Wanandi; Komputerio Akbar (Devotion : Journal of Research and Community Service, 2026)
Information Technology Service Management (ITSM) is a strategic approach in managing and providing quality IT services to users. In the era of digital transformation, organizations face complex challenges in managing IT services that are increasingly critical to business operations. The ITIL (Information Technology Infrastructure Library) framework has become the most widely adopted international standard for ITSM implementation. This study aims to comprehensively analyze the main components of ITIL 4, the implementation process, the challenges faced, and the impact of implementation on the effectiveness of IT services in the organization. The research method used is a systematic literature study with case analysis of ITIL implementation in various industrial sectors and higher education institutions. Data sources were obtained from 25 indexed scientific journals, official ITIL documentation, and case study reports from organizations that have implemented ITIL. The results show that proper ITIL implementation can improve the quality of IT services by up to 40%, reduce downtime by up to 35%, increase first-call resolution rate by up to 50%, and significantly increase user satisfaction. The study also identifies critical factors for the successful implementation of ITIL, including executive sponsorship, effective change management, human resource competence, and selection of the right tools. The findings of the research provide practical contributions to organizations planning to adopt ITIL and theoretical contributions in the development of the body of knowledge.